(untitled) (Islamic Sciences Journal, 2023)
The research includes the life and happiness of a Muslim woman, that she is honored and honored under Islam, that she has full rights and has duties, and that those duties she performs willingly, no one compels her to perform her performance, and that what she owes from the religious costs she carries out well and has her reward and repay from Allah like what a man has Without missing anything from it, Allah Almighty equated them in that. who said: (Men have a share of what they have acquired, and women have a share of what they have acquired). The Muslim woman, whether she is a mother, sister, wife, or daughter, and that she is not charged with work and earning livelihood and alimony, and that the man has to spend money for her and manage her. As for the western or western women, she lives a difficult life full of cruelty and distress and that she is not free and dear and does not have any happiness as she is. She is charged with earning and providing for herself and her children, If we compare the life of a Muslim woman, whether she is in the West or in Muslim countries, we find that she enjoys love and affection from her husband, children, and brothers and sisters. Her life is guaranteed and she is kept well will and far from all evil, unlike the western woman, whose life was full of problems and troubles and she did not gain sympathy and tenderness from anyone, so she remained confused.